2012
DOI: 10.1073/pnas.1215172109
|View full text |Cite
|
Sign up to set email alerts
|

Fine-tuning synaptic plasticity by modulation of Ca V 2.1 channels with Ca 2+ sensor proteins

Abstract: Modulation of P/Q-type Ca 2+ currents through presynaptic voltage-gated calcium channels (Ca V 2.1) by binding of Ca 2+ /calmodulin contributes to short-term synaptic plasticity. Ca 2+ -binding protein-1 (CaBP1) and Visinin-like protein-2 (VILIP-2) are neurospecific calmodulin-like Ca 2+ sensor proteins that differentially modulate Ca V 2.1 channels, but how they contribute to short-term synaptic plasticity is unknown. Here, we show that activity-dependent modulation of presynaptic Ca V 2.1 channels by CaBP1 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
55
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(55 citation statements)
references
References 46 publications
0
55
0
Order By: Relevance
“…In transfected superior cervical ganglion neurons, facilitation requires the expression of Ca V 2.1 channels and is blocked by the IM-AA mutation (14). Moreover, expression of CaS proteins can change the mode of synaptic plasticity from facilitation to depression and vice versa (17,18). The results presented here and in the accompanying report on hippocampal synapses provide, to our knowledge, the first reported evidence that regulation of Ca V 2.1 channels by CaS proteins is required for normal facilitation and depression in native synapses, and that failure of regulation of Ca V 2.1 channels has crucial consequences for in vivo physiology of nerve and muscle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In transfected superior cervical ganglion neurons, facilitation requires the expression of Ca V 2.1 channels and is blocked by the IM-AA mutation (14). Moreover, expression of CaS proteins can change the mode of synaptic plasticity from facilitation to depression and vice versa (17,18). The results presented here and in the accompanying report on hippocampal synapses provide, to our knowledge, the first reported evidence that regulation of Ca V 2.1 channels by CaS proteins is required for normal facilitation and depression in native synapses, and that failure of regulation of Ca V 2.1 channels has crucial consequences for in vivo physiology of nerve and muscle.…”
Section: Discussionmentioning
confidence: 99%
“…The Ile-Met→Ala-Ala (IM-AA) mutation prevents this synaptic plasticity by altering the interaction of Ca V 2.1 channels with CaS proteins (14). Other CaS proteins can displace calmodulin from their common regulatory site, enhance either facilitation or inactivation of the Ca 2+ current, and thereby control the direction and amplitude of synaptic plasticity in cultured superior cervical ganglion neurons (15)(16)(17)(18). Although previous studies revealed that regulation of Ca V 2.1 channels by CaS proteins can induce and regulate short-term synaptic plasticity in transfected neurons in cell culture, whether this mechanism makes an important contribution to short-term synaptic plasticity in native synapses has remained unknown.…”
mentioning
confidence: 99%
“…Ca 2+ -dependent facilitation and inactivation of P/Q-type Ca 2+ currents correlate with facilitation and rapid depression of synaptic transmission at the Calyx of Held (15)(16)(17)(18). Elimination of Ca V 2.1 channels by gene deletion prevents facilitation of synaptic transmission at the Calyx of Held (19,20 -dependent facilitation and inactivation of channel activity (22)(23)(24)(25)(26). Expression of these different CaS proteins with Ca V 2.1 channels in cultured sympathetic ganglion neurons results in corresponding bidirectional changes in facilitation and depression of the postsynaptic response (25,26).…”
mentioning
confidence: 99%
“…Elimination of Ca V 2.1 channels by gene deletion prevents facilitation of synaptic transmission at the Calyx of Held (19,20 -dependent facilitation and inactivation of channel activity (22)(23)(24)(25)(26). Expression of these different CaS proteins with Ca V 2.1 channels in cultured sympathetic ganglion neurons results in corresponding bidirectional changes in facilitation and depression of the postsynaptic response (25,26). Therefore, binding of CaS proteins to Ca V 2.1 channels at specific synapses can change the balance of CaS-dependent facilitation and inactivation of Ca V 2.1 channels, and determine the outcome of synaptic plasticity (27).…”
mentioning
confidence: 99%
“…Short-term and long-term modifications in synaptic strength are regulated by the frequency and pattern of presynaptic spiking (2-5). Regulation of voltage-gated Ca 2+ channel type 2.1 (Ca V 2.1) by calmodulin (CaM) and related Ca 2+ sensor (CaS) proteins causes Ca 2+ -dependent facilitation and inactivation of P/Qtype Ca 2+ currents (6-12) that results in short-term facilitation and rapid depression of synaptic transmission (9,(12)(13)(14). Deletion of the gene encoding Ca V 2.1 channels (15) or mutation of their CaS protein binding domain (12-14) impairs short-term synaptic plasticity.…”
mentioning
confidence: 99%